Observation of new magnetic ground state in frustrated quantum antiferromagnet spin-liquid system Cs₂CuCl₄ - Hyeong-Jin Kim; Haines, C.R.S.; Liu, C.; Sae Hwan Chun; Kee Hoon Kim; Yi, H.T.; Sang-Wook Cheong; Siddharth S. Saxena (Физика низких температур, 2017)
Cs₂CuCl₄ is known to possess a quantum spin-liquid phase with antiferromagnetic interaction below 2.8 K. We report the observation of a new metastable magnetic phase of the triangular frustrated quantum spin system Cs₂CuCl₄ induced by the application of hydrostatic pressure. We measured the magnetic properties of Cs₂CuCl₄ following the application and release of pressure after 3 days. We observed a previously unknown ordered magnetic phase with a transition temperature of 9 K. Furthermore, the recovered sample with new magnetic ground state possesses an equivalent crystal structure to the uncompressed one with antiferromagnetic quantum spinliquid phase.